The Complete Book on Ferrous, Non-Ferrous Metals with Casting and Forging Technology - Board N. (Delhi, National Institute of Industrial Research, 2005)
The heat treatment of ferrous (steel) Metal is based on the physical metallurgical principles which relate processing properties and structure. In heat treatment, the processing is most often entirely thermal and modifies only structure. The principles which govern heat treatment of metals and alloys are applicable, of course, to both ferrous and non-ferrous alloys. However, in practice there are sufficient differences to make it convenient to emphasize as separate topics the peculiarities of the alloys of each class in their response to heat treatment. The Present book covers production processes, heat treatment and other valuable details of ferrous and non-ferrous metals. This is very helpful book for new entrants, technocrats, research scholars, libraries and existing units.